2023
DOI: 10.1111/eci.13958
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional and national burden of alopecia areata and its associated diseases, 1990–2019: A systematic analysis of the Global Burden of Disease Study 2019

Abstract: Background No study to date has concomitantly reported the global burden of alopecia areata (AA) and its associated diseases. Methods The crude and age‐standardized rates of prevalence (ASPR), incidence (ASIR) and years lived with disability (YLDs) of AA were extracted from the global burden of disease, injuries and risk factors study (GBD) database between 1990 and 2019 for 204 countries and territories. We stratified the analysis by global region, nation, sex, age and sociodemographic index (SDI) to dissect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…1 According to the global burden of disease (GBD) database 1990-2019, the age-standardised disability adjusted life years (DALYs) rate of AA was 7.51 (4.73-11.14) per 100,000 persons globally. 2 AA often manifests as an abrupt loss of hair in clearly defined areas. The affected region typically consists of a round-shaped patch of alopecia that may be widespread or localised.…”
Section: Introductionmentioning
confidence: 99%
“…1 According to the global burden of disease (GBD) database 1990-2019, the age-standardised disability adjusted life years (DALYs) rate of AA was 7.51 (4.73-11.14) per 100,000 persons globally. 2 AA often manifests as an abrupt loss of hair in clearly defined areas. The affected region typically consists of a round-shaped patch of alopecia that may be widespread or localised.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke is induced by sudden infarction of brain vessels, with a high rate of morbidity and mortality. It is reported that ischemic stroke is the second highest cause of mortality worldwide, leading to 5.9 million deaths and 102 million disabilities. , Currently, the golden rule of clinical treatment for ischemic stroke is to restore blood reperfusion in the ischemic penumbra, ensuring that brain tissue can replenish blood oxygen and rescue damaged neurons, but survivors still are at high risk for disability, neurological deficits and other infections due to ischemia-reperfusion ending up with neuronal injury. , Therefore, there is an urgent need for the development of more feasible methods for ischemic stroke treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the leading cause of death and long-term disability worldwide, which imposes a great burden on global health. 1 Despite significant advancements in the past decades, critical gaps persist in the management of stroke and its subtypes(i.e. large artery atherosclerosis, cardioembolic stroke, or small artery occlusion).…”
Section: Introductionmentioning
confidence: 99%